2018
DOI: 10.1039/c8dt01298a
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing intramolecular cobalt–imidazole coordination with a remote methyl group in the backbone of a cofactor B12–protein model

Abstract: This communication describes the stabilizing effect (ΔΔG° = -4 kJ mol) of a remote methyl group in the backbone of a cobalamin-enzyme mimic on intramolecular imidazole-cobalt coordination. For this purpose, two B derivatives with an appended imidazole base were synthesized and analysed with spectrophotometric pH titrations. Qualitative conformation analysis of the backbone structure suggests that a thermodynamically unfavoured gauche interaction in the base-off form of a model containing an (R)-configured CH g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Electrocatalytic four electrons reduction of O2 to H2O by cobalt porphyrins has been extensively studied so far not only because of its biological relevance, but also due to its technological significance such as in fuel cells [21,22]. Furthermore, the studies of cobalamin and its derivatives/analogues have significantly contributed to increase the popularity of Co(II) complexes [23][24][25][26]. It was also found that the reactivity of axial ligation of cobalt porphyrin play a pivotal role in a number of bio-and 'bio-inspired' catalytic transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Electrocatalytic four electrons reduction of O2 to H2O by cobalt porphyrins has been extensively studied so far not only because of its biological relevance, but also due to its technological significance such as in fuel cells [21,22]. Furthermore, the studies of cobalamin and its derivatives/analogues have significantly contributed to increase the popularity of Co(II) complexes [23][24][25][26]. It was also found that the reactivity of axial ligation of cobalt porphyrin play a pivotal role in a number of bio-and 'bio-inspired' catalytic transformations.…”
Section: Introductionmentioning
confidence: 99%